2021
DOI: 10.1101/2021.02.11.430718
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymetallic nodules are essential for food-web integrity of a prospective deep-seabed mining area in Pacific abyssal plains

Abstract: Polymetallic nodule fields provide hard substrate for sessile organisms on the abyssal seafloor between 3,000 and 6,000 m water depth. Deep-seabed mining targets these mineral-rich nodules and will likely modify the consumer-resource (trophic) and substrate-providing (non-trophic) interactions within the abyssal food web. However, the importance of nodules and their associated sessile fauna in supporting food-web integrity remains unclear. Here, we use seafloor imagery and published literature to develop highl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Sponge grounds, known as areas where sponges reach densities of 0.5-1 m -2 (still image surveys 68 ) to 0.03-0.1 m -2 (video surveys 40 ), usually exhibit an increased associated benthic diversity and biomass when compared to adjacent non-sponge habitats 41 . Sponges typically enhance the complexity of habitats by increasing the (three-dimensional) hard surface area available for other fauna to interact (e.g., settle, reproduce, and/or hide 37,[69][70][71][72] ). For instance, at the Schulz Bank seamount large demosponges like Geodia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Sponge grounds, known as areas where sponges reach densities of 0.5-1 m -2 (still image surveys 68 ) to 0.03-0.1 m -2 (video surveys 40 ), usually exhibit an increased associated benthic diversity and biomass when compared to adjacent non-sponge habitats 41 . Sponges typically enhance the complexity of habitats by increasing the (three-dimensional) hard surface area available for other fauna to interact (e.g., settle, reproduce, and/or hide 37,[69][70][71][72] ). For instance, at the Schulz Bank seamount large demosponges like Geodia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Connectivity between deep seabed habitats and broader ecosystem functioning are poorly understood. Research suggests that polymetallic nodules play an important part in food-web integrity in benthic ecosystems (Stratmann et al, 2021), and that in situ carbon fixation on abyssal plains and hydrothermal vents and their contribution to surface productivity is greater than previously expected (Levin et al, 2020b). Climate change is already having a profound impact on ocean chemistry and temperature, even in the deepest parts of our oceans, and may be contributing to changes to the distribution or migration of species, loss of habitat and food availability (Levin et al, 2020b).…”
Section: The Risks To Biodiversity and Ecosystem Services Should Deep Seabed Mining Proceedmentioning
confidence: 99%
“…In fact, Veillette et al (2007) identified 73 protozoan and 17 metazoan taxa attached to polymetallic nodules from the CCZ and Vanreusel et al (2016) showed that even mobile benthos might benefit from the presence of nodules as their densities were higher in areas with nodules compared to nodule-free areas. To quantify the role of polymetallic nodules for trophic and non-trophic interactions in the CCZ, Stratmann et al (2021) recently presented a highly-resolved interaction-web model: When the authors removed the nodules from the interaction web, they detected knock-down effects causing the loss of 17.9% of all taxa and 30.6% of all network links. Their detailed model estimated that 4% of all meiobenthos (i.e., benthos >32 µm), 50% of the macrobenthos (i.e., benthos >250 µm/ 500 µm), 45% of the invertebrate megabenthos (benthos >1 cm), and 0.5% of the fish were missing and the most impacted phyla were Bryozoa, Cnidaria, Platyhelminthes, and Porifera.…”
Section: Introductionmentioning
confidence: 99%